Applying the "˜BUCS' strategy in grade IV of Elementary School to learn main ideas and supporting details - Rambe, Riris Nurkholidah; Nasution, Belladina; Supartinah, Supartinah (Diksi, 2022)
This study aims to improve learning activities and the ability to determine the main and supporting ideas through the application of the BUCS earning strategy that includes Baca (read), Uraikan (transform), Cermati (observe), Sampaikan (convey) in grade IV of Islamic Elementary School (IES) SDIT Nurul "˜Ilmi, Medan. Classroom action research employed in this study refers to the Kemmis & Taggart model whose cycle includes planning, observation, and reflection. The research subjects were 21 students of fourth graders of the IES, whiles the objects studied were learning activities and the ability to determine the main ideas and supporting details in reading texts in the Indonesian language. Data were collected through observation sheets and tests and were analyzed by using qualitative descriptive analysis. The results show that (1) the means for learning activities of Grade IV students at SDIT Nurul "˜Ilmi likely indicated a modest increase from 72% to 77%. (2) Besides, students' skills in identifying main ideas and supporting details likewise experienced a noticeable upturn. The means for this variable in the pretest was 57, which then escalated to 61 in cycle 1 and 89 in cycle 2, respectively.English translation. Keywords: BUCS learning strategy, main ideas and supporting details, elementary school